การศึกษาการกลายพันธุ์ของยีน SCN5A และการศึกษา Linkage analysis ในยีน SCN5A, KCND2 และ KCND3 ในครอบครัวใหลตาย - ปฐมวดี ญาณทัศนีย์จิต (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Sudden Unexplained Death Syndrome ( SUDS) (or Lai-tai) shares the same ECG pattern as Brugada syndrome : right bundle branch block and ST segment elevation in V1 to V3. Brugada syndrome is a genetic disorder with the inheritance pattern of autosomal dominant (using the ECG pattern and unexplained sudden death as phenotype) and associate with cardiac sodium channels (SCN5A) mutations . To detect the SCN5A mutation in SUDS, we performed the direct sequencing in one family with some evidence of linkage to SCN5A. However, the direct sequencing in eight reported mutations (exon 5,12,17,18,23 and 28 )in this family failed to demonstrate the mutations. We concluded that the mutations in SUDS maybe the novel mutations different from previously reported mutations or maybe caused by other mutations such as KCND2 and KCND3 gene. We performed the linkage study in four families in three gene, SCN5A, KCND2 and KCND3 and could not find the linkage to these genes. we concluded that these genes were not associated with SUDS .Further studies are needed to elucidate the molecular mechanism of this syndrome.